2016
DOI: 10.1016/j.tcb.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced EGFR Trafficking: Mechanisms, Functions, and Therapeutic Implications

Abstract: Epidermal growth factor receptor (EGFR) has fundamental roles in normal physiology and in cancer, making it a rational target for cancer therapy. Surprisingly, however, inhibitors that target canonical, ligand-stimulated EGFR signaling have proven to be largely ineffective in treating many EGFR-dependent cancers. Recent evidence indicates that both intrinsic and therapy-induced cellular stress triggers robust, non-canonical pathways of ligand-independent EGFR trafficking and signaling, which provides cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
181
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(187 citation statements)
references
References 122 publications
(136 reference statements)
4
181
0
Order By: Relevance
“…Van Dommelen et al, for example, reported an association between cetuximab response and extracellular vesicles [74]. It is known that EGFR signalling is highly regulated by intracellular trafficking, and molecules involved in this process can affect EGFR signalling and EGFR localisation [32,75]. To this end, Annexin A1 has shown to be required for the formation of ILVs in multivesicular bodies (MVBs) that sequester ligandbound EGFR away from the limiting membrane [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Dommelen et al, for example, reported an association between cetuximab response and extracellular vesicles [74]. It is known that EGFR signalling is highly regulated by intracellular trafficking, and molecules involved in this process can affect EGFR signalling and EGFR localisation [32,75]. To this end, Annexin A1 has shown to be required for the formation of ILVs in multivesicular bodies (MVBs) that sequester ligandbound EGFR away from the limiting membrane [21].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the type of ligand, ligand-activated EGFR can signal from various subcellular compartments unless it is sequestered on intraluminal vesicles (ILVs) in the lumen of multivesicular endosomes where it is delivered to lysosomes for degradation [32]. ANXA1 has been suggested to be important for the formation of the intraluminal vesicles and thus termination of EGFR signalling in cervical cancer [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…For example, lysosomal-associated protein transmembrane 4B (LAPTM4B) binds to inactive EGFR on endosomes, which participates in the initiation of autophagy (16,28). Furthermore, cellular stress conditions with p38 activation have been shown to affect autophagy (15). Distinct from activation with ligands, EGFR phosphorylated by p38 is sorted to lipid lysobisphosphatidic acid (LBPA)-rich perinuclear MVBs upon a UVC or cisplatin stimulation, demonstrating that canonical and non-canonical and PC-9 cells were pretreated with 10 µM SB or 30 nM TM, followed by the 100 µM CDDP treatment for 6 h. In all data, the localization of total EGFR and phosphor-serine EGFR was detected by a confocal microscopy analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of cells with these stimuli induces the clathrin-mediated endocytosis (CME) of EGFR, which is triggered by the activation of p38, in a TK-independent manner. It has recently been reported that the TK-independent functions of EGFR contribute to the initiation of autophagy and prevention of TNF-α-induced apoptosis (10,15,16). Therefore, a more complete understanding of the TK-independent functions of EGFR under cellular stress conditions is needed in the field of EGFR biology and EGFR-targeting therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…The non-canonical regulation of EGFR has also been investigated in the last decade. We and others demonstrated that pro-inflammatory cytokines, including tumor necrosis factor- (TNF-), and other cellular stresses induced the serine/threonine phosphorylation and internalization of EGFR (12)(13)(14)(15)(16)(17). This type of EGFR endocytosis depends entirely on p38 activation and clathrin recruitment.…”
mentioning
confidence: 99%